Nanocellulose Xerogels With High Porosities and Large Specific Surface Areas - Yamasaki, Shunsuke; Sakuma, Wataru; Yasui, Hiroaki; Daicho, Kazuho; Saito, Tsuguyuki; Fujisawa, Shuji; Isogai, Akira; Kanamori, Kazuyoshi (Frontiers in Chemistry, 2019)
Xerogels are defined as porous structures that are obtained by evaporative drying of wet gels. One challenge is producing xerogels that are structurally comparable to supercritical-dried aerogels with a high porosity and large specific surface area. Herein, we report on cellulose xerogels with a truly aerogel-like porous structure. These xerogels have a monolithic form with porosities and specific surface areas in the ranges of 71%–76% and 340–411 m2/g, respectively. Our strategy is based on combining three concepts: 1) the use of a very fine type of cellulose nanofibers (CNFs) with a width of approximately 3 nm as the skeletal component of the xerogel; 2) increasing the stiffness of wet CNF gels by reinforcing the inter-CNF interactions to sustain their dry shrinkage; and 3) solvent-exchange of wet gels with low-polarity solvents, such as hexane and pentane, to reduce the capillary force on drying. The synergistic effects of combining these approaches lead to improvements in the porous structure in the CNF xerogels.